(untitled) (European Journal of Interdisciplinary Research and Development, 2025)
This methodological guide explores the mechanisms for attracting international students to higher education institutions in Uzbekistan. It provides a comprehensive analysis of theoretical foundations, strategic approaches, and the creation of a favorable academic environment for foreign students. Additionally, the guide examines the role of modern digital tools, branding strategies, and international collaboration in enhancing Uzbekistan’s global educational image. By integrating innovative educational technologies and improving student support services, this work aims to offer practical recommendations for increasing the competitiveness and attractiveness of Uzbekistan’s higher education sector in the global market.